Implementation of the conventional seven-level single-phase symmetrical cascaded h-bridge MLI based on PSIM - Hassan Salman Hamad (Institute of Advanced Engineering and Science, 2020)
Researchers have found interest in the multilevel inverters (MLI) owing to the low total harmonic distortion (THD) associated with their output voltage, as well as their low electromagnetic interference (EMI). The MLI represents an effective and feasible solution for enhancing power demand and minimizing AC waveforms’ harmonics as they generate a preferred level of output voltage as inputs from varying levels of DC voltages. In this paper, the performance of a seven-level cascaded H-bridge MLI with an asymmetrical number of power switches was evaluated. The simulation performance is shown to validate the operating principle of the single-phase cascaded H-bridge inverter. To control the MLI, a pulse width modulation approach was utilized. The operating principle of the MLI was verified via simulation using PSIM software.